Understanding Genetic Algorithms In Architecture - Latifi, Mohammad; Mahdavinezhad, Mohammad Javad; Diba, Darab (The Turkish Online Journal of Design Art and Communication, 2016)
Genetic algorithms (GAs) are computational techniques based upon evolution. They have been recently introduced in architecture to study present complexities in form and function. Despite growing trends and inclinations to use GAs, there is not an organized study and instruction about its usage in architecture. This library research, while examining the structure of GAs, seeks answers to these questions: 1. What is the necessity of GAs in architecture today? 2. Are GAs used to meet special needs of architecture or are they merely complex forms? 3. Haw can GAs come to our assistance in design? And last but not least 4. Does GAs serve reality or unreal abstract forms of an imaginative world!? To answer these questions, the present research studies GAs in architecture and other disciplines. It also investigates their functions in architecture and finally explains introductory parametric operations in this field.
Keywords: Genetic Algorithm; Genetic Operators; Parametric Architecture; Optimization